Assessing Profitability Of Small-Scale Cocoa-Goat Mixed-Farming In West Sulawesi, Indonesia - Pereira, Abrao; Paterson, Stacey; McMahon, Peter; Guest, David; Purwantara, Agus; Ann Toribio, Jenny (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 15 No 1 (2021): Vol.15, No.1, 2021, 2021)
Cocoa is a key crop for small-scale farmers in Sulawesi, Indonesia. Decline in cocoa yield and cocoa price fluctuation have negatively affected the income of small-scale farmers. An approach to address the sustainability of small-scale cocoa farming is to diversify the household income via cocoa-goat mixed farming. This study aimed to assess whether cocoa-goat mixed farming was a viable and profitable enterprise for small-scale farmers in West Sulawesi by using cost benefit analysis (CBA). Three CBA models were developed to compare profitability of an existing medium-scale cocoa-goat mixed farm located in West Sulawesi with hypothetical small-scale cocoa monoculture and cocoa-goat mixed farming. The CBAs were informed by an interview using structured questionnaire and literature search. The principal CBA assessment criterion was net present value (NPV) while benefit cost ratio (BCR) and internal rate of return (IRR) were supplementary. Sensitivity analysis measured the impact of changes in key parameters on profit. Over a 25-year production cycle, the medium-scale cocoa goat mixed farm is a profitable enterprise, earning an estimated profit of USD 90,403. At small-scale level, the findings suggest that engaging in small-scale cocoa goat mixed farming has potential to increase household income by 27% of profit from the cocoa monoculture.